Brain Metastasis in Pediatric Patients with Osteosarcoma - Jacob Murphy; R. Taylor Sundby; Erin E. Resch; Ruyan Rahnama; Kathryn M. Lemberg; Alexandre Maalouf; Aditya Suru; Jason Fixler; Brian H. Ladle; Daniel S. Rhee; Adam S. Levin; Aparna Pallavajjala; et al. (Current Oncology)
Background: Brain metastases in pediatric osteosarcoma are infrequent but associated with a dire prognosis. Methods: This retrospective study examined six pediatric patients at Johns Hopkins Hospital who developed brain metastases from osteosarcoma between April 2015 and November 2023. Results: Median survival post-brain metastasis was 2.5 months. The patients underwent various treatments, including chemotherapy, surgery, and radiation. Despite these interventions, outcomes were uniformly fatal. Notably, one patient survived over 13 months post-brain metastasis with a treatment regimen of cabozantinib and nivolumab along with surgical resection and radiation, highlighting the potential efficacy of multimodal treatment regimens. This case demonstrated changes in the immune microenvironment, hinting at an anti-tumoral response, although no histologic response was observed. Conclusions: These findings emphasize the critical need for vigilant clinical monitoring, especially in patients with new neurological symptoms. The study highlights the diagnostic challenges and the rapid progression of brain metastases, underscoring the necessity for further research. Prospective studies and clinical trials focusing on novel therapeutic strategies are essential to improve outcomes. Disease biology studies examining tumor features across primary, pulmonary, and brain metastatic sites may offer insights into the mechanisms of metastasis and potential therapeutic targets, providing a foundation for better management of this devastating complication.